Pendampingan Pengawetan dan Pengemasan Sayuran Pasca Panen Sebagai Strategi Pendorong Perekonomian Petani Precet - Widayani, Heni; Layla, Ria Dhea; Naschicuddin, Achmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The impact of Covid-19 pandemic has made vegetable farmers suffer losses due to hampered distribution of fresh vegetables. Fresh vegetables that have been harvested but not immediately processed will easily wilt which will reduce the selling value. This phenomenon occurs in many vegetable plantation areas, one of which is in the Dusun Precet. Vegetable farming products are a source of livelihood for the people of Dusun Precet who mostly work as vegetable farmers. The main problem for vegetable farmers is that the price of vegetables is cheap at harvest time, so that farmers experience losses. Post-harvest vegetable processing and packaging training is one solution that can be done to overcome this problem. Processing and packaging of fresh vegetables is expected to make harvested vegetables last longer and local vegetables can be marketed more widely. In addition, team from UIN Maulana Malik Ibrahim Malang also provide socialization regarding the nutrient of frozen vegetables as still same as the fresh one if packaged properly and correctly. This program is expected to be able to encourage the economy of the people in Dusun Precet in the future.